An ancient retrovirus-like element contains hot spots for SINE insertion. - Cantrell, M A (2001)
Vertebrate retrotransposons have been used extensively for phylogenetic analyses and studies of molecular evolution. Information can be obtained from specific inserts either by comparing sequence differences that have accumulated over time in orthologous copies of that insert or by determining the presence or absence of that specific element at a particular site. The presence of specific copies has been deemed to be an essentially homoplasy-free phylogenetic character because the probability of multiple independent insertions into any one site has been believed to be nil. Mys elements are a type of LTR-containing retrotransposon present in Sigmodontine rodents. In this study we have shown that one particular insert, mys-9, is an extremely old insert present in multiple species of the genus Peromyscus. We have found that different copies of this insert show a surprising range of sizes, due primarily to a continuing series of SINE (short interspersed element) insertions into this locus. We have identified two hot spots for SINE insertion within mys-9 and at each hot spot have found that two independent SINE insertions have occurred at identical sites. These results have major repercussions for phylogenetic analyses based on SINE insertions, indicating the need for caution when one concludes that the existence of a SINE at a specific locus in multiple individuals is indicative of common ancestry. Although independent insertions at the same locus may be rare, SINE insertions are not homoplasy-free phylogenetic markers.